Ketimpangan Wilayah Antar Kabupaten/Kota Di Provinsi Lampung - Farida Aliyatul Asy’ariati; Heru Wahyudi; Asih Murwiati; Tiara Nirmala; Arivina Ratih Yulihar Taher (Goodwood Publishing, 2022)
In addition to economic growth, regional inequality is also an important issue for the development of every country. Theoretically and supported by many empirical studies, it is proven that high economic growth has an impact on regional inequality. Regional inequality is related to the income received by people in a country. Panel data is the data used in this study with the best method, namely the best Random Effect Model using the Eviews 9.0 analysis tool for regression. Based on the results of data processing, the average food expenditure and the number of poor people have a significant and positive effect on regional inequality in districts/cities in Lampung, while the average non-food expenditure and the average length of schooling have no significant effect. Economic inequality between regions is a common aspect of the economic activities of a region. Inequality arises due to differences in the content of natural resources and differences in demographic conditions found in each region. So that the ability of a region in the development process will also be different. Therefore, in each region, there is a developed region and a backward region.